Ethnographie d’un film commémoratif - Isabelle Becuywe (Conserveries Mémorielles)
In 2009 a French cultural institution, owing an audiovisual archives, celebrated its fortieth anniversary. Two ethnologists were thus made responsible for producing an exhibition in less than six months. This finally resulted in a 20-minute film. Looking at the technical and ethical issues that have emerged throughout the making of the film, this paper presents the different steps and problems we faced. It also analyses this achievement regarding its display conditions and its reception by the public. Two issues are particularly addressed. Firstly: what is the historicity of such a film? what does its temporality involve? Secondly: what does the exhibition production process does reveal of forty years of film archiving?In the 2003 UNESCO Convention defined “immaterial heritage”. I work in anthropology on storytelling using digital technologies in France and Quebec. Studying oral archive institutions and online inventories Internet projects, I question the concept of immaterial heritage.